The Effectiveness of Interactive Learning Media in Hadith Instruction at Madrasah: A Quasi-Experimental Study - Abdul Rahim; La Ode Sahrin Djalia (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study examines the effectiveness of interactive learning media in Hadith instruction at Madrasah Aliyah Al Qayyum Hendea. The research was motivated by the continuing dominance of conventional, teacher-centered approaches in Hadith learning, which often limit student engagement, motivation, and understanding of the meaning and relevance of Hadith in everyday life. In response to the growing demand for pedagogical innovation in the digital era, this study investigates whether interactive learning media can improve the quality of the learning process and outcomes in Hadith instruction. This research employed a quantitative approach with a quasi-experimental design involving an experimental class and a control class. The experimental class was taught using interactive learning media, while the control class received conventional instruction. Data were collected through pre-test and post-test, classroom observation, and student response questionnaires. The data were then analyzed using descriptive and inferential statistics to determine differences in learning outcomes, student activity, and responses toward the learning process. The findings reveal that interactive learning media significantly improved students’ learning outcomes, classroom participation, and positive responses to Hadith instruction. Students in the experimental class demonstrated higher post-test scores, greater learning mastery, more active involvement during instruction, and stronger motivation compared to those in the control class. These results indicate that interactive media not only enhance cognitive achievement but also enrich the learning experience by making Hadith instruction more engaging, contextual, and meaningful. In conclusion, interactive learning media are effective in improving the quality of Hadith instruction in madrasahs. The study recommends the integration of interactive media into Islamic religious education to support more student centered, relevant, and adaptive learning practices in the contemporary educational context.